(untitled) (Academicia Globe: Inderscience Research, 2022)
Examples of didactic games used in primary school in the field of education are given. The purpose of this article is to improve the arbitrariness of such mental processes in children as attention and memory, since game tasks develop in children ingenuity, resourcefulness, quick wits, judgment, inference, organization, endurance, the art of observing the rules of the game, subordinate their horizons to the interests of the team.